2020
DOI: 10.3390/foods9050617
|View full text |Cite
|
Sign up to set email alerts
|

Post-Ingestive Sensations Driving Post-Ingestive Food Pleasure: A Cross-Cultural Consumer Study Comparing Denmark and China

Abstract: Culture is one of the main factors that influence food assessment. This cross-cultural research aimed to compare Chinese and Danish consumers in their post-ingestive drivers of Post-Ingestive Food Pleasure (PIFP). We define PIFP as a “subjective conscious sensation of pleasure and joy experienced after eating”. We conducted two in-country consumer studies in Denmark (n = 48) and in China (n = 53), measuring post-ingestive sensations and PIFP using visual analogue scale, for three hours following consumption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
(112 reference statements)
0
11
0
Order By: Relevance
“…Food-related pleasure (and reward) within the appetite space has primarily focused on wanting and liking of food, prior to or during consumption, respectively. Though it has been argued that food-derived reward also depends on the mental and bodily well-being experienced after eating [ 44 ], this element has not been researched until recently [ 60 , 61 , 62 ]. ‘Post-ingestive food pleasure’ is defined as a subjective conscious sensation of pleasure and joy experienced after eating [ 62 ] and is driven by both mental and physical sensations, which can be measured via interoception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food-related pleasure (and reward) within the appetite space has primarily focused on wanting and liking of food, prior to or during consumption, respectively. Though it has been argued that food-derived reward also depends on the mental and bodily well-being experienced after eating [ 44 ], this element has not been researched until recently [ 60 , 61 , 62 ]. ‘Post-ingestive food pleasure’ is defined as a subjective conscious sensation of pleasure and joy experienced after eating [ 62 ] and is driven by both mental and physical sensations, which can be measured via interoception.…”
Section: Discussionmentioning
confidence: 99%
“…Though it has been argued that food-derived reward also depends on the mental and bodily wellbeing experienced after eating [44], this element has not been researched until recently [60][61][62]. 'Post-ingestive food pleasure' is defined as a subjective conscious sensation of pleasure and joy experienced after eating [62] and is driven by both mental and physical sensations, which can be measured via interoception. Interoception functions as a basis for self-awareness and subjective feelings, and can provide insights into the extended appetite experience.…”
Section: A Focus On Post-ingestive Well-beingmentioning
confidence: 99%
“…These results suggest similarities but also distinct subtleties in the cultural constructs of PIFP in Denmark and in China. Duerlund et al (2020) overall suggested that focusing on food pleasure as a post-ingestive measure provides valuable output, deeper insights into what drives food pleasure, and, importantly, takes us beyond the processes only active during the actual eating event.…”
Section: Appetite Pleasure and Ingestion Sensationsmentioning
confidence: 99%
“…Furthermore, in the present volume, Laaksonen et al (2020) in Finnish and Chinese contexts looked at oat product concepts [ 14 ]. The authors present that oats and oat-based products were increasingly popular among consumers and the food industry, and whilst studies exist on the sensory characteristics of oats as such, previous studies focusing specifically on the pleasantness of oats, and especially investigations of a wide range of oat products eaten by European and Asian consumers, are scarce.…”
Section: A Synopsis Of Special Issue Researchmentioning
confidence: 99%
See 1 more Smart Citation